Association of Epstein-Barr virus (EBV) with lung cancer: meta-analysis - Chen, Yizhuo; Liu, Tianhua; Xu, Ziqing; Dong, Ming (Frontiers in Oncology, 2023)
Abstract Objective: To analyze the potential link between EBV infection and lung cancer by reviewing existing studies and determining the prevalence of EBV in individuals diagnosed with lung cancer. Method: A literature search was conducted in an online database to estimate the prevalence of EBV using random effects models and calculate the pooled odds ratio from case-control studies. Results: Among 886 lung cancer patients, the overall prevalence of EBV infection was 44.36%. The prevalence varied across different pathological types of lung cancer, with LELC showing the highest rate at 81.08%. The association between EBV infection and lung cancer was stronger in China than in other regions, and non-small cell lung cancer was more strongly associated with EBV than small cell lung cancer. Conclusion: EBV infection increases the risk of lung cancer by over four times and is associated with pathological type, lymphatic infiltration, and degree of differentiation, particularly in LELC. Regional and racial differences exist in the correlation between EBV-infected lung cancer, with the Asian population showing greater susceptibility. Tissue adjacent to the tumor was used as a more accurate control for determining the relationship between EBV infection and lung cancer.